Experimental investigation of fatigue behavior for adhesively-bonded GFRP/steel joints. (15th June 2020) - Jiang, Zhengwen; Wan, Shui; Fang, Zhi; Song, Aiming
Highlights: Fatigue behavior of the adhesive GFRP/steel DLJ was experimentally investigated. Stiffness degradation models applicable to the adhesive GFRP/steel DLJ were presented. Crack propagation law for the adhesive GFRP/steel DLJ was provided. The difference between fatigue behavior of the adhesive GFRP/steel and GFRP/GFRP DLJ was identified. Abstract: The fatigue behavior of an adhesively bonded glass fiber-reinforced polymer (GFRP)/steel double-lap joint (DLJ) under cyclic tensile loading with load ratio R  = 0.1 was experimentally studied. Results in terms of failure mode, F-N curve, stiffness degradation law, crack initiation and propagation laws were obtained. Linear and nonlinear models of stiffness degradation and a mathematical model of the crack growth rate were developed for the adhesive GFRP/steel DLJ under fatigue loading. The fatigue performance of adhesive GFRP/steel DLJ was compared with that of adhesive GFRP/GFRP DLJ to identify the differences between these behaviors. The results demonstrated that the stiffness degradation law of the adhesive GFRP/steel DLJ can be objectively and accurately characterized by the nonlinear stiffness degradation model in terms of the equivalent shear stiffness. The crack initiation life and the ratio between the crack initiation life and fatigue life increased with the deceasing maximum applied load. The fatigue life of the GFRP/steel DLJ was more sensitive to the variation in the maximum applied load compared with that of the GFRP/GFRP DLJ. Moreover, the decaying rate of stiffness and the interfacial crack propagation rate for the GFRP/steel DLJ under fatigue loading were larger than those for the GFRP/GFRP DLJ.